Regulation of human feto-placental endothelial barrier integrity by vascular endothelial growth factors: competitive interplay between VEGF-A165a, VEGF-A165b, PIGF and VE-cadherin - Pang, Vincent; Bates, David O.; Leach, Lopa (Portland Press, 2017)
The human placenta nourishes and protects the developing fetus whilst influencing maternal physiology for fetal advantage. It expresses several members of the VEGF family including the pro-angiogenic/pro-permeability VEGF-A165a isoform, the anti-angiogenic VEGF-A165b, placental growth factor (PIGF) and their receptors, VEGFR1 and VEGFR2. Alterations in the ratio of these factors during gestation and in complicated pregnancies have been reported; however the impact of this on feto-placental endothelial barrier integrity is unknown. This study investigated the interplay of these factors on junctional occupancy of VE-cadherin and macromolecular leakage in human endothelial monolayers and the perfused placental microvascular bed. Whilst VEGF-A165a (50 ng/ml) increased endothelial monolayer albumin permeability (p<0.0001), equimolar concentrations of VEGF-A165b (p>0.05) or PlGF (p>0.05) did not. Moreover, VEGF-A165b (100 ng/ml; p<0.001) but not PlGF (100 ng/ml; p>0.05) inhibited VEGF-A165a-induced permeability when added singly. PlGF abolished the VEGF-A165b-induced reduction of VEGF-A165a mediated permeability (p>0.05); PlGF was found to compete with VEGF-A165b for binding to Flt-1 at equimolar affinity. Junctional occupancy of VE-cadherin matched alterations in permeability. In the perfused microvascular bed, VEGF-A165b did not induce microvascular leakage but inhibited and reversed VEGF-A165a-induced loss of junctional VE-cadherin and tracer leakage. These results indicate that the anti-angiogenic VEGF-A165b isoform does not increase permeability in human placental microvessels or HUVEC primary cells and can interrupt VEGF-A165a-induced permeability. Moreover, the interplay of these isoforms with PIGF (and s-flt1) suggests that the ratio of these three factors may be important in determining the placental and endothelial barrier in normal and complicated pregnancies.